A log-barrier Newton-CG method for bound constrained optimization with complexity guarantees. (18th April 2020) - O'Neill, Michael; Wright, Stephen J
Abstract: We describe an algorithm based on a logarithmic barrier function, Newton's method and linear conjugate gradients that seeks an approximate minimizer of a smooth function over the non-negative orthant. We develop a bound on the complexity of the approach, stated in terms of the required accuracy and the cost of a single gradient evaluation of the objective function and/or a matrix-vector multiplication involving the Hessian of the objective. The approach can be implemented without explicit calculation or storage of the Hessian.